2011
DOI: 10.1115/1.4003235
|View full text |Cite
|
Sign up to set email alerts
|

Novel IGV Designs for Centrifugal Compressors and Their Interaction With the Impeller

Abstract: In centrifugal compressors, variable inlet guide vanes (IGVs) are used to control the mass flow rate with negligible change in pressure ratio and shaft speed. The efficient operation of IGVs is limited to the range of aerodynamic stability of their vane profiles. Thin symmetric profiles, which are usually used, tend to exhibit flow separation already at low setting angles, resulting in a rapid decrease in the global efficiency. Three different guide vane profiles, including a symmetric reference profile, a two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 10 publications
2
21
0
Order By: Relevance
“…1 Many works have been carried out to investigate the influence of IGVs on energy performance, 2,3 internal flow field, 4,5 and unsteady interaction 6,7 for centrifugal compressors.…”
Section: Introductionmentioning
confidence: 99%
“…1 Many works have been carried out to investigate the influence of IGVs on energy performance, 2,3 internal flow field, 4,5 and unsteady interaction 6,7 for centrifugal compressors.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach is the application of Inlet Guide Vanes (IGVs). A positive vane angle produces preswirl in the direction of impeller rotation and, thus, reduces compressor work at a given revolutions‐per‐minute (RPM) …”
Section: Introductionmentioning
confidence: 99%
“…Early experimental and computational fluid dynamics (CFD) studies showed that introducing preswirl increases the efficiency at lower mass flow rates and improves the surge limit. More recent studies have applied CFD simulations to investigate features such as performance, unsteady interactions between the IGVs and the impellers, pressure fluctuations at large IGV angles, and the effect of IGV geometry . A review of preswirl in from IGVs can be found in the work of Liu et al…”
Section: Introductionmentioning
confidence: 99%
“…Coppinger and Swain [2] demonstrated the test techniques and resulting analyses of the existing design of inlet guide vanes systems for industrial centrifugal compressor, and conducted some predictions of the performance of the improved IGVs system design. Mohseni et al [3] presented three different novel IGVs designs for centrifugal compressors and the results showed that the s-cambered profile was preferred for applications with positive prewhirl. Cui [4] and Oro et al [5] focused on the unsteady flow for centrifugal compressors with inlet guide vanes, and analyzed the unsteady flow structures, periodic interaction, and wake transport.…”
Section: Introductionmentioning
confidence: 99%